Zeolites catalyst from oil palm ash for petrochemical industries - Noor Atikah, Mohd Badruddin (2013)
The nature of business is the application of “Waste to Wealth” concept which is converting industrial waste into a valuable product. The industrial waste can be converted and become an added value product to a certain industries. The product that we are producing is zeolites catalysts for petrochemical industries using oil palm ash. The synthesis of zeolites using oil palm ash will be more environmental friendly. It’s also will increase the performance of the zeolites in the process. Besides that, synthesis of zeolite using chemical would be very expensive compare to what we have here, a waste as main composition of silica that is used to replace some of the usage of chemical. The present market for Malaysia is about 9000 metric tons per annum. About five detergent manufacturers and three oil and gas companies are users of zeolite A. However, a large number of companies and petrochemical industries in Malaysia are potential users or currently using imported zeolites. This is the opportunities to start a company that produce zeolite in Malaysia. The location for this business is in Gebeng, Pahang because of the availability of raw material and also located at the centre of petrochemical industry in Malaysia which is in Pahang and Terengganu. The purpose of this business plan is to obtain capital for starting-up this company. The total capital needed for the start-up of this company is RM 1,200,000. This includes all equipment and others fixed assets such as a warehouse for operation location, the renovation, furniture and electric appliances such as computers and so forth. From the financial analysis we are be able to have return on investment in the third year of business. Based on the analysis conducted which comprises of market analysis and financial analysis mostly, this business has the potential to grow in Malaysia.